A comparative study of the metabolic profile, insulin sensitivity and inflammatory response between organically and conventionally managed dairy cattle during the periparturient period. (11th June 2014) - Abuelo, A.; Hernández, J.; Benedito, J. L.; Castillo, C.
<x content-type="archive" xml:space="preserve">Abstract</x> The number of organically managed cattle (OMC) within the European Union has increased tremendously in the last decade. However, there are still some concerns about animals under this farming system meeting their dietary requirements for milk production. The aim of this study was to compare the metabolic adaptations to the onset of lactation in three different herds, one conventional and two organic ones. Twenty-two conventionally managed cattle (CMC) and 20 from each organic farm were sampled throughout the periparturient period. These samplings were grouped into four different stages: (i) far-off dry, (ii) close-up dry, (iii) fresh and (iv) peak of lactation and compared among them. In addition, the results of periparturient animals were also compared within each management type with a control group (animals between the 4th and 5th months of pregnancy). Metabolic profiles were used to assess the health status of the herds, along with the quantification of the acute phase proteins haptoglobin and serum amyloid A, insulin and the calculation of different surrogate indices of insulin sensitivity. Generalised linear mixed models with repeated measurements were used to study the effect of the stage, management type or their interaction on the serum variables studied. The prevalence of subclinical ketosis was higher in OMC, although they showed better insulin sensitivity, a lower degree of inflammation and less liver injury, without a higher risk of macromineral deficiencies. Therefore, attention should be paid on organic farms to the nutritional management of cows around the time of calving in order to prevent the harmful consequences of excessive negative energy balance. Moreover, it must be taken into account that most of the common practices used to treat this condition in CMC are not allowed on a systematic basis in OMC.